MathCoder2 Pretraining Enhances Adversarial Robustness in Sub-3B Math Models - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: Does the MathCoder2 pretraining approach improve robustness against adversarial perturbations in competition-level math problems for models under 3B parameters. 17 claims were extracted from source literature; 2 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.2/10. This report is a machine-generated literature synt
Machine-generated literature synthesis.